2015
DOI: 10.5897/ajpp2014.4228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aqueous root bark extract of Citropsis articulata (Swingle Kellerman) on sexual function in male rats

Abstract: About 80% of the world's population uses herbal medicine for the treatment of various health conditions. Erectile dysfunction is one of the conditions commonly treated using traditional herbs on large scale. In this study, our goal was to determine the safety and effects of the aqueous root bark extract of Citropsis articulata on sexual function in male Wistar rats. This study aimed to carry out phytochemical analysis of the aqueous root bark extract of C. articulata, conduct acute toxicity test to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Sesamine ( 4 ) is the major lignan in sesame seeds and has been confirmed to be safe. It attenuated reactive oxygen species and nitric oxide production in zebra fish (LD 50 ) [ 99 ]. Toxicity studies with zingerone ( 5 ) and gingerol ( 6 ) have shown that they are safe [ 100 , 104 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sesamine ( 4 ) is the major lignan in sesame seeds and has been confirmed to be safe. It attenuated reactive oxygen species and nitric oxide production in zebra fish (LD 50 ) [ 99 ]. Toxicity studies with zingerone ( 5 ) and gingerol ( 6 ) have shown that they are safe [ 100 , 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…species and nitric oxide production in zebra fsh (LD 50 ) [99]. Toxicity studies with zingerone (5) and gingerol (6) have shown that they are safe [100,104].…”
Section: Zingiber Ofcinalementioning
confidence: 99%